Prognostic advantage of optimal medical therapy is not cancelled in hospitalized heart failure patients receiving regular hemodialysis. (14th October 2021) - Takada, T; Jujo, K; Kishihara, M; Shirotani, S; Watanabe, S; Abe, T; Yoshida, A; Minami, Y; Hagiwara, N
Abstract: Background: As the first-line medications, renin-angiotensin-aldosterone system inhibitor (RAASi) and β-blocker provide prognostic benefits in patients with heart failure (HF) and reduced left ventricular ejection fraction (LVEF). However, the negative inotropic effect of these drugs may destabilize the hemodynamics during hemodialysis (HD) and become prognostically controversial in patients receiving regular HD. Indeed, prior studies have reported the cancellation of the favorable prognostic effects of RAASi and β-blocker in patients with HD. However, it is totally unknown whether the guideline-directed medical therapy affects the prognosis in HF patients receiving regular HD. Purpose: We aimed to evaluate the prognostic impact of RAASi and β-blocker on the cardiovascular (CV) events in HF patients on regular HD. Methods: This observational study initially included 1, 930 consecutive patients who were hospitalized due to HF and discharged alive. Of these, 151 patients who received regular HD were ultimately analyzed. They were classified into 3 groups depending on the prescribing medications at discharge; patients who received none of RAASi or β-blocker (None group: N=19), either RAASi or β-blocker (Either group: N=56), and both RAASi and β-blocker (Both group: N=76). The primary endpoint was a composite of CV death and readmission due to HF. Results: During the observation period of median 501 (interquartile range: 197–954) days, the primary endpoint occurred in 61 patients (40%). Kaplan-Meier analysis showed the highest rate of composite endpoint in the None group (log-rank for trend: p<0.001, Figure). After adjusting for covariates of age, sex, LVEF, and systolic blood pressure and heart rate at discharge, the hazard ratio (HR) for a composite endpoint was significantly lower in the Either group or Both group than that in the None group [HR: 0.19, 95% confidence interval (CI): 0.08–0.45; HR: 0.16, 95% CI: 0.06–0.42, respectively]. Conclusions: The prescription of RAASi or β-blocker at discharge was associated with lower adverse CV event rates in patients on regular HD who were hospitalized for HF. In order to improve long-term prognosis of HF patients on HD, we should consider the prescription of RAASi or β-blocker for them if hemodynamics during HD is affordable. Funding Acknowledgement: Type of funding sources: None.